Intracellular sodium elevation reprograms cardiac metabolism - Dunja Aksentijević (Nature Portfolio, 2020)
The failing heart is characterised by both alterations in mitochondrial metabolism and an elevation of cytosolic sodium. Here, the authors use 23Na NMR and metabolic profiling to show these are related, and that elevation in intracellular Na reprograms cardiac substrate utilisation via effects on mitochondrial Na/Ca exchange.